Morphological Evaluation of Head and Face in North Indian Population (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
Forensic anthropology plays a vital role in not only identification such as racial identification, sex and age but also in identification of skeleton. Various ecological, geographical and ethnical fac tors as well as age and gender determine the dimensions of human body. Cephalometry was undertaken on 1600 healthy volunteers of either sex of age group 0-40 years. The dominant head form was dolichocephalic (47.62%) followed by mesocephalic (41.31%). Brachycephalic was rare in both sexes. Male dolichocephalics predominated. The correlation between age and sex in dolichocephalic, mesocephalic, and brachycephalic was highly significant (p value
Keywords: Cephalometry; Craniofacial forms; Cephalic index; Prosopic index; Nasal index